IRRIGATION REGIME FOR POMEGRANATE (PUNICA GRANATUM L.) ON LIGHT STONE-GRAVEL GRAY SOILS (BASED ON THE EXAMPLE OF THE FERGHANA REGION) - S.X.Zakirova; R.F.Akbarov; Sh.E.Yursunova; Z.M.Razhavalieva (American Journal Of Agriculture And Horticulture Innovations, 2023)
In the article, given the water shortage in the glen regions, where light stone-gravel sierozems are widespread, it is important to effectively use these regions and place plants taking into account the soil and climatic conditions of the region and area. water demand, therefore, taking into account the water shortage in the conditions of light stone-gravel gray soils of the Fergana region, it is necessary to study the features of irrigation methods, timing and standards of pomegranate plants that are resistant to erosion.